Assessing the Impact of Leverage Ratio on Banking Efficiency in Indonesia - Kelvin Lily; Dwi Nastiti Danarsari (Eduvest - Journal of Universal Studies, 2024)
This study analyzes the significance of the leverage ratio on the efficiency of banking companies with the aim of assessing the readiness and suitability of banking companies in facing the implementation of Basel 4 or Basel 3.1. Data from 47 banking companies in Indonesia from the period 2008 to 2023 were used as material for this study. The data used in the research were analyzed using the Dynamic Stochastic Frontier (DSF) method. This method allows for more accurate efficiency analysis by avoiding assumptions of technology at different times. The researchers hypothesize that banking companies with a leverage ratio level higher than the minimum limit applied in BASEL have better efficiency, and the results of this study show corresponding results within the leverage ratio limit of 20%.